(untitled) (Journal of the College of Basic Education, 2023)
The process of adsorption of some pollutants from solutions on the surfaces of solids is known for its efficiency. The adsorption mechanism was studied on the surface of the powder particles of these rocks, and the obtained experimental results show that the adsorption isotherms are of the L4 type according to the Giles classification and follow the Langmuir adsorption equation. And that the dolomite rocks contain a high percentage of 68.66% of MgCO3 and a variable percentage of alumina and silica, albeit relatively few, which made them rich in effective adsorption centers that are divided into negative effective groups and positive effective groups. It was observed that there is a gradient in the adsorption isotherms, which was interpreted as a clear indication of the formation of multiple layers of adsorbent particles on the surface of the adsorbent material, as it is an indication of a change in orientation in some cases. The adsorption was better when treated with a temperature of 600ºC than when treated with a temperature of 900ºC, as the amount of adsorbent material decreased significantly.